Prevalence of COVID-19 in flood relief centre - Suriya Kumareswaran; Siti Umairah Muhadi; Jeyanthini Sathasivam; Bala Murali Sundram (International Journal of Public Health Science (IJPHS), 2023)
Since the beginning of 2020, people all around the world have been struggling with the impacts of the COVID-19 pandemic. Concurrently, major flooding and a pandemic have struck numerous regions of the world. As a result, relief centres for flood victims have been established in the affected regions. There is a risk of COVID-19 infection spreading among flood victims and workers at flood relief centres due to the enormous number of flood victims. This study focused on the Johor, Malaysia flood catastrophe. From the 1st to the 16th of January 2022, a cross-sectional study was conducted in johor flood relief centres using secondary data from E notification and COVID-19-line listing. 1,531 flood victims were examined for COVID-19 and Rapid antigen testing was performed. 711 victims were asymptomatic, whereas 820 victims were symptomatic. Six patients were identified as positive. During audits of multiple evacuation centres, few concerns were found. There was no sufficient ventilation, there was no distribution of face masks to victims, and there were no daily health checks. COVID-19 preventive measures in all evacuation centres need to be practiced and given attention by all occupants and agencies.